Tight glycemic control with insulin does not affect skeletal muscle degradation during the early post-operative period following pediatric cardiac surgery - Fisher, Jeremy G. (Pediatr Crit Care Med, 2015)
OBJECTIVE: Critical illness is associated with significant catabolism and persistent protein loss correlates with increased morbidity and mortality. Insulin is a potent anti-catabolic hormone; high-dose insulin decreases skeletal muscle protein breakdown in critically ill pediatric surgical patients. However, insulin's effect on protein catabolism when given at clinically utilized doses has not been studied. The objective was to evaluate the effect of post-operative tight glycemic control and clinically-dosed insulin on skeletal muscle degradation in children after cardiac surgery with cardiopulmonary bypass. DESIGN: Secondary analysis of a two-center, prospective randomized trial comparing tight glycemic control with standard care. Randomization was stratified by study center. PATIENTS: Children 0-36 months who were admitted to the ICU after cardiac surgery requiring cardiopulmonary bypass. INTERVENTIONS: In the tight glycemic control (TGC) arm, insulin was titrated to maintain blood glucose between 80-110 mg/dL. Patients in the control arm received standard care. Skeletal muscle breakdown was quantified by a ratio of urinary 3-methylhistidine to urinary creatinine (3MH:Cr). MAIN RESULTS: A total of 561 patients were included: 281 in the TGC arm and 280 receiving standard care. There was no difference in 3MH:Cr between groups (TGC 249 ± 127 vs. standard care 253 ± 112, mean ± standard deviation in μmol/g, P=0.72). In analyses restricted to the TGC patients, higher 3MH:Cr correlated with younger age as well as lower weight, weight-for-age z-score, length, and body surface area (P<0.005 for each), and lower post-operative day 3 serum creatinine (r=-0.17, P=0.02). Sex, prealbumin, and albumin were not associated with 3MH:Cr. During urine collection, 245 patients (87%) received insulin. However, any insulin exposure did not impact 3MH:Cr (t-test, P=0.45), and there was no dose-dependent effect of insulin on 3MH:Cr (r=-0.03, P=0.60). CONCLUSION: Though high-dose insulin has an anabolic effect in experimental conditions, at doses necessary to achieve normoglycemia, insulin appears to have no discernible impact on skeletal muscle degradation in critically ill pediatric cardiac surgical patients.